Studying The Concept Of Maqasid Al-Shari'ah Al-Juwayni In The Book Of Al-Burhan Fi Usul Al-Fiqh - Nasiri (Al Iman: Jurnal Keislaman dan Kemasyarakatan, 2022)
Abu al-Ma'ali al-Juwayni, a high-caliber jurist is well known as Imam al-Haramayn. His appearance brought forward a work on original usul al-fiqh which was different from the written style of the previous usul al-fiqh books as well as provided tremendous influence to the writing of the later books. His description about the law methodology, in his work namely al-Burhan fi Usul al-Fiqh, was a valuable original finding that differentiates him from the other authors of the usul books. One of his original ideas which was his first breakthrough in the field of usul al-fiqh was the concept of maqasid al-shari'ah, to which he divided it into two parts: "the unwritten maqasid" that was achieved through istiqra' way and “written maqasid” that was achieved through coherence (qarinah) which were divided into contextual coherence (qarinah haliyyah) and verbal coherence (qarinah maqaliyyah) through the ways of exception (istithna ') and specialization (takhsis).